2011
DOI: 10.1371/journal.pone.0025880
|View full text |Cite
|
Sign up to set email alerts
|

Intranasal Application of S. epidermidis Prevents Colonization by Methicillin-Resistant Staphylococcus aureus in Mice

Abstract: Methicillin-resistant S. aureus emerged in recent decades to become a leading cause of infection worldwide. Colonization with MRSA predisposes to infection and facilitates transmission of the pathogen; however, available regimens are ineffective at preventing MRSA colonization. Studies of human nasal flora suggest that resident bacteria play a critical role in limiting S. aureus growth, and prompted us to query whether application of commensal resident bacteria could prevent nasal colonization with MRSA. We es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
54
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(56 citation statements)
references
References 19 publications
1
54
0
1
Order By: Relevance
“…Although bacterial antagonism against S. aureus has previously been investigated (41,43,47,48), our data suggest that there are additional variables to consider when prophylactic countermeasures are being designed; in order to lower the risk of development of SSTI, one must lower S. aureus colonization levels but must be cognizant of other nasal bacterial inhabitants, especially from the phylum Proteobacteria. Additionally, a reduction of specific bacteria in noncarriers, including Propionibacterium and S. epidermidis, correlates with SSTI development (Fig.…”
Section: Discussionmentioning
confidence: 88%
“…Although bacterial antagonism against S. aureus has previously been investigated (41,43,47,48), our data suggest that there are additional variables to consider when prophylactic countermeasures are being designed; in order to lower the risk of development of SSTI, one must lower S. aureus colonization levels but must be cognizant of other nasal bacterial inhabitants, especially from the phylum Proteobacteria. Additionally, a reduction of specific bacteria in noncarriers, including Propionibacterium and S. epidermidis, correlates with SSTI development (Fig.…”
Section: Discussionmentioning
confidence: 88%
“…These findings may explain the bacterial competition for human nasal cavity colonization. This competition could be either Grampositive versus Gram-negative bacteria or within the same group of bacteria as was shown in an animal model by Park et al [15]. They investigated whether the applica- Table 1.…”
Section: Discussionmentioning
confidence: 99%
“…They suggested that application of commensal bacteria with antibiotics could represent a more effective strategy to prevent MRSA colonization [15]. Development of S. epidermidis-dominated microbiota may either protect an individual patient from subsequent S. aureus colonization or be an intermediate stage in succession to a nasal microbiota dominated by S. aureus.…”
Section: Proteus Mirabilis 1 -mentioning
confidence: 99%
“…Application of corynebacteria or Staphylococcus epidermidis have already been shown to eliminate S. aureus colonization in the nares in a significant proportion of the population 11,12 . Studies into specific strains that can competitively exclude undesirable members of the host flora, through techniques such as the one described here, may therefore lead to future therapeutics.…”
Section: Discussionmentioning
confidence: 99%